Displaying curves and surfaces in Unity3D system - Khiew, Jian Bin (2019)
FVRML is a tool created in efforts to provide a function-based shape modeling and visualization tool. It is currently provided to students in NTU as part of a Computer Science coursework project, Computer Graphics & Visualization, and other related studies.This study is to investigate the extend of Unity3D’s capability as a platform to support FVRML’s features, the advantages over BS Contact and ultimately to conclude whether Unity3D could be used to provide a new coursework software tool to NTU students. This study investigates Unity3D’s ability to create curves, surfaces and solids using parametric and implicit functions and to display them in a virtual scene. In addition, providing an intuitive UI system to edit input parameters and a standalone software application for multiple platforms. Participants were then invited to compare FVRML + BS Contact to the new Unity3D software.